Pembangunan Sistem Perubahan Kebutuhan Menggunakan Improved Framework - Widya Bayu Wicaksono; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Requirement change is an inevitable in software development activity. It can happen when stakeholders change their requirements. By the time requirements change becomes more complicated in software development. Requirements change are hardly achieved well because the lack of communication among stakeholders and software developer. Requirements change impact can affect process, cost, and schedule of software development. In this research a mehod and framework will be explained to resolve this problem. The framework includes all the process that required in requirement change management. The framework start with stakeholder write down what their needs, then analyzed, and finally some vote will be done to determine wether requirement change is worth to be implemented or not. Past research used to solve this problem will be explained too.There is also a method to count impact occurred when requirement change will be implemented. This method count time to implement, cost, and time left before the deadline come. Some data taken to support this problem in requirement change. The data is taken from Inagata Technosmith Software house in Malang city.